The Influence of Differentiation Strategy, Learning Motivation on Students' Critical Thinking Skills on the Ecosystem Theme - Raudhatul Hasna; Nor Hafizah Indah Fauziah; Siti Fatonah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the influence of differentiation strategies and learning motivation on critical thinking skills of fifth-grade students of Madrasah Ibtidaiyah on the theme of Ecosystems, as well as the interaction between the two. This study used a quantitative approach with an ex post facto method. The sample consisted of 41 students from grades VA and VB. The instrument was a critical thinking skills test, and the data were analyzed using a two-way ANOVA test. The results showed that differentiation strategies had a significant influence on students' critical thinking skills (p = 0.030), which indicates the importance of implementing learning tailored to students' needs, interests, and abilities. In contrast, learning motivation did not show a significant effect (p = 0.812), as did the interaction between differentiation strategies and learning motivation (p = 0.859). These results indicate that an appropriate and differentiated learning approach has a greater influence on the development of critical thinking skills than internal learning motivation. Therefore, teachers are advised to implement adaptive and responsive strategies to optimally support students' critical thinking skills.